Cytomegalovirus retinitis in a patient of granulomatosis with polyangiitis on long-term immunosuppressants - Reddy, Subhakar (BMJ Case Rep, 2021)
A 69-year-old male patient presented to the retina clinic with a sudden decrease in vision in his right eye since 1 day. He was a known case of granulomatosis with polyangiitis and was on systemic immunosuppression for the past 3 years. The best-corrected visual acuity (BCVA) in his right eye was 20/60 and he has no perception of light in the left eye. Fundus examination revealed the presence of retinitis lesions in the right eye and total optic atrophy in the left eye. A vitreous biopsy was done and the PCR was found to be positive for cytomegalovirus (CMV). He was treated with intravitreal ganciclovir injections. Subsequently, the retinitis lesions regressed and BCVA in the right eye improved to 20/40. This case report elaborates on the risks of the development of opportunistic ocular infections in patients receiving long-term systemic immunosuppressants and the need for regular ocular examinations in such cases.